MEDIA PEMBELAJARAN MULTIMEDIA BAHASA ISYARAT DAYAK NGAJU UNTUK ANAK TUNA RUNGU: Dayak Ngaju Sign Language Multimedia Learning Media For Deaf Children - Sulistyowati; Suparno; Rosmiati; Sam'ani; Bayu Pratama Nugroho; Ade Irawan (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
In the field of education there are schools that handle Children with Special Needs (ABK), namely children who significantly (meaningfully) experience abnormalities/deviations (physical, mental-intellectual, social, emotional) in the process of growth/development compared to other children of the same age including children deaf people so that they require special education services or are sent to special schools. One of the uses of technology in the field of special education for children with hearing impairments is in the form of processes in learning sign language such as finger alphabet sign language, number sign language and word dictionary sign language. The introduction of sign language lessons often has difficulties in communicating with students because these students not only come from the city center but some come from remote villages. understand the local language. The system development method applied in conducting this research is by adopting the concept of multimedia modeling. The final result of this research is in the form of multimedia learning media for Dayak Ngaju sign language which can be utilized by children with special needs, namely deaf children and also teachers.